2020
DOI: 10.1177/1099636220909763
|View full text |Cite
|
Sign up to set email alerts
|

Bending and free vibration analysis of sandwich plates with functionally graded soft core, using the new refined higher-order analysis model

Abstract: This study presents a new higher-order refined analysis model for static and free vibration analysis of a sandwich plate with soft functionally graded material core. The governing equations are derived from equilibrium differential equations of motions. The accuracy and convergence of the present model and numerical solution are validated versus available results. Variable length width ratios, thickness ratios between skins and core and span-to-thickness of sandwich plates have been studied. Obtained results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 61 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Then, they investigated the impact of various parameters (i.e., geometrical parameters, porosity parameter, the porosity distribution pattern, the thickness of the porous core, and compressibility of pore‐fluid) on natural frequencies. Ye et al [ 15 ] presented a high‐order modified model for analyzing the free and static vibrations of a sandwich plate with a core made of soft materials and evaluated the ratio of variable length, the ratio of thickness between the shell and the core, and the ratio of the span‐to‐thickness of sandwich plates. The obtained results indicated that the proposed model can provide higher accuracy for sandwich plates with a soft material core compared to conventional sandwich models and those based on the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they investigated the impact of various parameters (i.e., geometrical parameters, porosity parameter, the porosity distribution pattern, the thickness of the porous core, and compressibility of pore‐fluid) on natural frequencies. Ye et al [ 15 ] presented a high‐order modified model for analyzing the free and static vibrations of a sandwich plate with a core made of soft materials and evaluated the ratio of variable length, the ratio of thickness between the shell and the core, and the ratio of the span‐to‐thickness of sandwich plates. The obtained results indicated that the proposed model can provide higher accuracy for sandwich plates with a soft material core compared to conventional sandwich models and those based on the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight multi-layered structures, including bilayers, trilayers, and sandwich plates which are made of soft materials have emerged as promising structures in different technological fields such as marine, automotive, civil, and mechanical engineering (Ye et al, 2021). The other important factor in these types of applications is controlling the structures’ behavior using smart materials for example, shape memory polymer, and hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al 56 studied the vibration response of the FGM sandwich plate via Reddy’s displacement fields. Ye et al 57 introduced a new HSDT model for flexure and vibration response of the FGM sandwich plate via the FEM approach. Fang et al 58 examined the free vibration of rotating FGM nanobeams via nonlocal models Euler–Bernoulli and Timoshenko beam theories.…”
Section: Introductionmentioning
confidence: 99%